Bush's policy toward Latin America - Hsiang, Antonio C. (2003)
Indicates that the Bush administration has focused its Latin American policy on three goals that look past the current financial woes afflicting the southern common market, Mercosur. Sees these goals as, consolidating the region as a strategic partner, accommodating challenges from the left, and alleviating nacroterrorism problems. Analyzes the administration's politics in these three basic areas as they have been affected by the 9/11/01 attacks on America and how they are likely to be perceived as the war on terror proceeds.